Tasawur Pemikiran Saintifik Ibn al-Haytham (Sains Humanika, 2014)
This article has two main purposes. First, to identify the sources of the formation of Ibn al-Haytham’s scientific thinking; and second, to analyze his scientific thinking worldview. The scientific thinking worldview refers to a holistic overview of the systematic and dynamic thinking in attaining knowledge which is attributed to Muslim scholar, Ibn al-Haytham. However, Ibn al-Haytham was accused by some Western scholars of being a secular minded Muslim scholar. Meanwhile some orientalists claimed that his school of thought was adapted only from Greek scholar, Aristotle. The question is, is it true that Ibn al-Haytham was a secular minded Muslim? Is it true that Ibn al-Haytham separates the divine element in implementing his scientific research? What are his sources of worldview? What about the worldview of his scientific thinking? All questions are answered by performing a content analysis on relevant secondary data. The discussion in this paper is divided into three main parts. Firstly, reviewing the biography of Ibn al-Haytham; secondly, identifying the sources of his scientific thinking worldview; and thirdly, analyzing the main elements of Ibn al-Haytham’s scientific thinking worldview. As a result, this paper concludes that the scientific thinking worldview of Ibn al-Haytham is characterized by three things: first, the Qur'an and the Hadith; second, philosophical thinking of the Greek scholars; and third, the influence of contemporary scholars. The overall analysis found that Ibn al-Haytham’s scientific thinking worldview are rooted from the strong faith in God, based on Islamic ethics and the desire of seeking the truth.
Keywords: Worldview; thinking; scientific; Ibn al-Haytham; element